RELATIONSHIP BETWEEN WOMEN'S PERCEPTIONS MARRIED WOMEN WITH PARTICIPATION IN THE USE OF INTRAUTERINE DEVICE USE IN PETANG VILLAGE BADUNG DISTRICT - Widiastrini, Ni Wayan; Senjaya, Asep Arifin; Budiani , Ni Nyoman (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
The low use of IUDs is due to several factors that can create a separate perception in married women about the IUD contraceptive method. The purpose of this study was to determine the relationship between married women's perceptions and participation in the use of intrauterine contraceptives in Petang Village, Badung Regency. This type of research is quantitative with a cross-sectional approach. Implementation in March to April 2024. The sample consisted of 47 people with a purposive sampling technique. Data collection using a questionnaire. The results of the study showed that 33 people (70.2%) had negative perceptions about the use of IUDs and 40 people (85.1%) did not use IUDs. Data analysis using the Chi-Square test obtained a p-value of 0.002 (<0.05). The conclusion of the study is that there is a relationship between married women's perceptions and participation in the use of intrauterine contraceptives in Petang Village, Badung Regency. Suggestions that can be given to the Petang I Health Center are to continue to provide counseling and include positive testimonials from individuals who have previously used IUDs.